2009
DOI: 10.1209/0295-5075/86/36004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a temperature-driven structural transformation in liquid bismuth

Abstract: The thermodynamic properties of liquid bismuth have been explored from the melting point to 1100 °C by high-resolution measurements of the density, the heat capacity and the static structure factor. These physical properties display a number of anomalies. In particular, we have observed evidence for the presence of a temperature-driven liquid-liquid structural transformation that takes place at ambient pressure. The latter is characterized by a density discontinuity that occurs at 740 °C. Differential thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 37 publications
11
87
0
Order By: Relevance
“…S5 displays obtained structural factors, S(q), of Bi liquid at 2 and 4 GPa up to 2,000 K. On heating to 1,050 K, all S(q) data contain a well-resolved small peak (q1 ) around 2.9Å −1 (corresponding to an interatomic spacing of ∼2.2Å) on the high-q side of the first sharp diffraction peak (FSDP) near 2.5Å −1 . This small peak has been observed in previous structural studies on Bi liquid at ambient pressure as a shoulder next to the FSDP (7,35,36). At 2 GPa, the small peak shifts on heating toward lower q, with diminishing intensity, until about 1,500 K, where it merges into the tail of the FSDP, becoming nonresolvable (Fig.…”
Section: Physicssupporting
confidence: 78%
“…S5 displays obtained structural factors, S(q), of Bi liquid at 2 and 4 GPa up to 2,000 K. On heating to 1,050 K, all S(q) data contain a well-resolved small peak (q1 ) around 2.9Å −1 (corresponding to an interatomic spacing of ∼2.2Å) on the high-q side of the first sharp diffraction peak (FSDP) near 2.5Å −1 . This small peak has been observed in previous structural studies on Bi liquid at ambient pressure as a shoulder next to the FSDP (7,35,36). At 2 GPa, the small peak shifts on heating toward lower q, with diminishing intensity, until about 1,500 K, where it merges into the tail of the FSDP, becoming nonresolvable (Fig.…”
Section: Physicssupporting
confidence: 78%
“…This feature is much broader than for lighter pnictogens (in particular Sb), and the absence of a well-defined first minimum complicates the analysis of coordination numbers. Also shown are the experimental (ND) results of Greenberg et al 15 The calculations reproduce the weak shoulder in S(Q) on the high-Q side of the first peak. Although the temperatures of the two sets of data are not identical, the agreement between theory and experiment is very encouraging.…”
Section: A Structure Factor Pair Distribution Function and Near-nementioning
confidence: 83%
“…Although the pair distribution functions show significant scatter, 14 there is clear evidence of a temperature-driven structural phase transition at 1013 K. 15 Inelastic neutron scattering (INS) measurements of the dynamical structure factor S(Q, ω) near the melting point of Bi show evidence of collective density excitations. 16,17 Bi + n cations 18 have been identified mass spectroscopically to n > 40, and photofragmentation of small Bi cluster cations has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…3) [2][3][4], in contrast to a symmetrical profile of simple liquid metals. The origin of the shoulder in S (Q) of liquid Bi was theoretically studied and it was found that an effective pair potential with a ridge in the repulsive component could reproduce the shoulder [5,6].…”
Section: Introductionmentioning
confidence: 98%